Analisis Penerapan Tata Kelola pada Usaha Mikro dan Kecil Menengah (UMKM) di Kelurahan Cikerai Cilegon - Surachman Surachman; Mulyani Mulyani; Dandy Rizky Oktariansyah; Iffuany Yaqaz; Markani Markani; Ranisa Sarbelia (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
MSME governance is one way to ensure that their business performance is sustainable and sustainable. Various methods are used to handle these governance problems. The aim of this Community Service (PKM) activity in the MSME sector is to implement MSME Governance within the Cikerai Village environment. The method used is conducting surveys and interviews with four stages starting from analysis to reporting. The results of PKM activities were carried out on the owner of the MSME business Mrs. Nay with the Nayy brand, who has a cassava chips snack business with financial and marketing constraints. After carrying out this activity, there was an understanding of MSME players, especially recording financial reports and developing traditional marketing into digital marketing